The politics of the anthropocene. Towards a common foundation of planetary responsibilities - Martínez de Bringas, Asier (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2023)
We will structure this work in four fundamental moments. A first moment, where we will expose different narratives of the Anthropocene. All of them start from different epistemological assumptions and approach different political proposals to think about the alternatives. We will also propose how we understand the Anthropocene and what potential it holds for thinking about transitions. In a second moment, we will talk about the ambivalence of the Anthropocene, that new condition that gives the human being the ability to bea geological force which implies an unprecedented power, but ambivalent, to the extent that it may imply its own destruction. The conscious understanding of the status of this ambivalence is a condition for the possibility of beginning to think about responsibilities in a different way. In a third moment, we will proposethe figure of the decentered anthropos as a symbolic expression to perceive, both the importance of the human being to think about other ways of living and transiting, as well as to apprehend the radical vulnerability that characterizes us, a necessary condition to think about any form of responsibility. We will layspecial emphasis on “biocentric paradigm”, as a place from which to enunciate the criticism of “anthropocentric paradigm”, its demands and proposals. Finally, and in a more proactive way, we will try to formulate the normative foundations of the responsibility(es) in the Anthropocene, starting from the moral universe that the ecosystemic fracture with which we live shows us.
Keywords: Anthropocene; politics; common; ecosystem; responsibility(s)